2012
DOI: 10.1155/2012/476457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture of Different Frequencies on the Release Profile of Endogenous Opioid Peptides in the Central Nerve System of Goats

Abstract: To investigate the release profile of met-enkephalin, β-endorphin, and dynorphin-A in ruminants' CNS, goats were stimulated by electroacupuncture of 0, 2, 40, 60, 80, or 100 Hz for 30 min. The pain threshold was measured using potassium iontophoresis. The peptide levels were determined with SABC immunohistochemisty. The results showed that 60 Hz increased pain threshold by 91%; its increasing rate was higher (P < 0.01) than any other frequency did. 2 Hz and 100 Hz increased met-enkephalin immunoactivities (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 31 publications
(38 reference statements)
4
41
0
Order By: Relevance
“…There were few reports in the literature as to the effects of EA 50 Hz as compared to those of EA 2 and 100 Hz. However, it has been recently reported that EA 60 Hz increases the pain threshold by a greater extent than any other frequency [87]. EA at a frequency of 60 Hz induced the simultaneous release of met-enkephalin, β -endorphin, and dynorphin-A in extensive analgesia-related nuclei and areas of the CNS, such as the periaqueductal gray, the paraventricular nucleus of the hypothalamus, the ventromedial nucleus of the hypothalamus, the dorsal raphe nucleus, and the nucleus raphe magnus, amongst others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were few reports in the literature as to the effects of EA 50 Hz as compared to those of EA 2 and 100 Hz. However, it has been recently reported that EA 60 Hz increases the pain threshold by a greater extent than any other frequency [87]. EA at a frequency of 60 Hz induced the simultaneous release of met-enkephalin, β -endorphin, and dynorphin-A in extensive analgesia-related nuclei and areas of the CNS, such as the periaqueductal gray, the paraventricular nucleus of the hypothalamus, the ventromedial nucleus of the hypothalamus, the dorsal raphe nucleus, and the nucleus raphe magnus, amongst others.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that EA at 60 Hz may contribute to optimal analgesic effects. The effects of EA at 50 or 60 Hz deserve to be studied further [87]. …”
Section: Discussionmentioning
confidence: 99%
“…At 0.5 h before and at 0, 2, 4, 6, 8, 12, and 24 h after EA, the pain threshold was measured on the center of the left flank using the method of potassium iontophoresis as described in detail by Cheng et al [16]. The pain threshold in the sham control was measured at 0.5 h before needle insertion and at 0 h after needle withdrawal.…”
Section: Methodsmentioning
confidence: 99%
“…The goat's brain, hypophysis, and a part of the adjacent spinal cord were immediately taken out of the skull and cervical vertebral canal. The brain was transected into 17 sections quickly with the method described by Cheng et al [16]. The nuclei and areas were identified according to the photographic atlas of the goat brain and the morphological characteristics of the neurons [17–19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation